Involvement of private actors in the provision of urban sanitation services; potential challenges and precautions a conceptual paper - Yeboah-Assiamah, E. (Management of Environmental Quality: An International Journal, 2015)
Purpose – The purpose of this paper is to use relevant models and theories to conceptualize theprospects and challenges associated with private sector involvement in the provision of sanitation and environmental services in urban settlements of developing African economies. Design/methodology/approach – The study adopts the public choice theory and principal-agent model in its conceptualization and analysis. Retrospective literature analysis within the qualitative research approach has been employed for the study. It draws extensively on existing classical theoretical and current empirical literature on privatization of urban sanitation services in developing countries. Findings – The study observes that privatization is a necessary tool for enhancing quality and responsive sanitation service delivery but there must be some mechanisms to prevent any latent challenges. The study also observes that the same problems associated with the public sector could transcend into the private sector if key measures are not taken into consideration. Practical implications – The process of privatizing or contracting out must ensure competition, enough communication to all stakeholders as well as involving expertise in the bidding process. The process also requires strict monitoring and supervision; these call for an appropriate legal framework to regulate privatization. The paper reminds urban administrators and policy makers to be circumspect in the privatization process. If the process of privatization is carried out effectively, urban sanitation services will be provided effectively and efficiently. Originality/value – The paper adapts the public choice and principal-agent model to assess privatization processes in developing African countries. This study will be of importance to urban administrators, public officials and policy makers in general. © Emerald Group Publishing Limited.
Keywords: Africa; Developing countries; Environmental services; Private sector; Privatization; Urban sanitation